2017
DOI: 10.1590/1518-8345.1774.2903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the application of therapeutic massage in children with cancer: a systematic review

Abstract: Objective: to learn about the effects of the use of therapeutic massage in children with cancer.Method: systematic review of controlled clinical trials The search was conducted in November 2014 in the following databases: Pubmed, CSIC, Dialnet, Scopus, Cochrane and PEDro. Inclusion criteria were: clinical trials, published in English or Spanish, analyzing the effects of massage on the different stages and types of childhood cancer (between 1 and 18 years old).Results: of 1007 articles found, 7 met the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
9
0
6
Order By: Relevance
“…In the other study about therapeutic massage, the participants reported significant reductions in pain after two sessions of therapeutic massage (p = 0.03) and in the worry after one session (p = 0.03) (46) . These findings are in line with two recent systematic reviews (53)(54) . The first review which aimed at understanding the effects of therapeutic massage on children with cancer www.scielo.br/reeusp Effectiveness of complementary therapies for the management of symptom clusters in palliative care in pediatric oncology: a systematic review Rev Esc Enferm USP • 2021;55:e03709 Health (NCCIH) as "a complementary health approach in which practitioners place their hands lightly on or just above a person, with the goal of helping to facilitate the person's own healing response" (61) .…”
Section: Therapeutic Massagesupporting
confidence: 93%
See 1 more Smart Citation
“…In the other study about therapeutic massage, the participants reported significant reductions in pain after two sessions of therapeutic massage (p = 0.03) and in the worry after one session (p = 0.03) (46) . These findings are in line with two recent systematic reviews (53)(54) . The first review which aimed at understanding the effects of therapeutic massage on children with cancer www.scielo.br/reeusp Effectiveness of complementary therapies for the management of symptom clusters in palliative care in pediatric oncology: a systematic review Rev Esc Enferm USP • 2021;55:e03709 Health (NCCIH) as "a complementary health approach in which practitioners place their hands lightly on or just above a person, with the goal of helping to facilitate the person's own healing response" (61) .…”
Section: Therapeutic Massagesupporting
confidence: 93%
“…has shown that the authors of the evaluated primary studies used different massage techniques (Swedish massage, effleurage, petrissage, frictions, pressure), obtaining benefits in symptoms (pain, nausea, stress, and anxiety reduction) and increase in leukocytes and neutrophils (53) . The second systematic review of clinical trials in the pediatric oncology population identified nine studies investigating the efficacy of therapeutic massage and found encouraging and beneficial evidence for various symptoms, especially for oncologic pain and anxiety (54) .…”
Section: Internal Validity Of the Included Studiesmentioning
confidence: 99%
“…In a systematic review on massage in children with cancer, the authors found seven articles that met inclusion criteria, although the authors of these studies used different massage techniques and reported on different symptoms [77]. The reviewers concluded that massage decreased pain, nausea, stress, and anxiety.…”
Section: Child and Adolescent Massage Therapymentioning
confidence: 99%
“…In a systematic review, on different massage techniques in oncologic children, the authors underlined in conclusions the beneficity of this maneuver in relieving pain -resulted from the cancer itself but also from the treatments side ef-fect -anxiety and nausea (8,11). Sleep disorder is common in pediatric oncology and there is an imperious need to target new treatments to improve this deficiency which often associate with daily time impairments as: anxiety, fatigue, and even psychological consequences (12,13,14).…”
Section: Results Of Literature Reviewmentioning
confidence: 99%
“…Moreover, a recent research (2014-2017) investigating the symptoms determined by intrathe-cal therapy/aspiration of bone marrow in children with cancer settled as well massage efficacy by decreasing pain and anxiety of those affected (21,22).…”
Section: Discussionmentioning
confidence: 98%